1968
DOI: 10.1139/v68-338
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance studies of tertiary phosphine hydrobromides

Abstract: Phosphorus and proton magnetic resonance data are presented for hydrobromides of 15 tertiary phosphines, of which 5 are trialkylphosphines, 5 are dialkylphenylphosphines, and 5 are diphenylalkylphosphines.The 31P chemical shifts of each of these series of phosphonium compounds are linearly related to the sum of the group contributions (g.c.) of the organic groups on the respective phosphines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…We found that the intermediate in the synthesis of II, methyl -nitrodimethylacrylate (III),7 could be efficiently deconjugated by kinetic protonation of the potassium salt IV, yielding the /3,7-unsaturated isomer V, in greater than 90% isolated yield. 10 The success of this deconjugation may reside in the orthogonal and therefore nonconjugated nature of IV, resulting from steric hindrance, as shown in VI. This substance V was smoothly reduced and hydrolyzed in one step with tin and hydrochloric acid to the racemic amino acid la (45%).…”
Section: References and Notesmentioning
confidence: 99%
“…We found that the intermediate in the synthesis of II, methyl -nitrodimethylacrylate (III),7 could be efficiently deconjugated by kinetic protonation of the potassium salt IV, yielding the /3,7-unsaturated isomer V, in greater than 90% isolated yield. 10 The success of this deconjugation may reside in the orthogonal and therefore nonconjugated nature of IV, resulting from steric hindrance, as shown in VI. This substance V was smoothly reduced and hydrolyzed in one step with tin and hydrochloric acid to the racemic amino acid la (45%).…”
Section: References and Notesmentioning
confidence: 99%
“…This constitutes a characteristic feature of phosphonium moieties and was termed a -effect. 47 Overall, these influences are reflected in a change of the spin system between 32e–h + featuring aryl- and methyl-substituents (ABMX 2 spin system) and those bearing alkyl-substituents 32a–d + (ABM 2 X spin system).…”
Section: Cationic Polyphosphorus Cages Featuring Alkyl- and Aryl-groumentioning
confidence: 99%
“…This can be explained in terms of a combination of a -effect and γ-effect ( vide infra ). 46 , 47 The resonances of the tetra-coordinated P atoms in aryl-substituted cations 36e–h + are shifted to higher field compared to those of the corresponding P atoms in cages 36a–d + . This is due to a positive mesomeric effect, namely the donation of π-electron density from the aryl substituents to the lobes of the anti-bonding σ*(P–P) orbitals at the phosphonium moiety.…”
Section: Cationic Polyphosphorus Cages Featuring Alkyl- and Aryl-groumentioning
confidence: 99%
“…Previous attempts to find correlations between Tuft's constants and observed chemical shifts either for uncomplexed tertiary phosphines [13] or for protonated tertiary phosphines [14] had failed. On the other hand, from the observed chemical shifts, group contributions had been empirically deduced 1131.…”
mentioning
confidence: 99%